Perceptual Cognitive Training Does Not Improve Clinical Outcomes at 4 and 12 Weeks Following Concussion in Children and Adolescents: A Randomized Controlled Trial. Issue 2 (13th March 2021) - Teel, Elizabeth; Brossard-Racine, Marie; Corbin-Berrigan, Laurie-Ann; Gagnon, Isabelle
Abstract : Objective: To determine whether a perceptual-cognitive training program using 3D-multiple object tracking (3D-MOT) can improve symptoms following acute pediatric concussion. Setting: Research laboratory within a pediatric trauma center. Participants: Children and adolescents ( n = 62, age= 13.27 ± 2.50) with diagnosed concussion. Design: Randomized controlled trial. Children were randomized into either 3D-MOT, 2048 game, or standard care-only groups. Participants and parents completed the Post-Concussion Symptom Inventory (PCSI) at baseline, 4, 8, and 12 weeks postinjury. Intervention participants completed either the 3D-MOT protocol or the 2048 game at 6 sessions between the baseline and 4-week assessment. Main Measures: A 3 (group) × 10 (time) mixed-model analysis of variance evaluated PCSI total scores. The rate of persistent postconcussive symptom (PPCS) was evaluated at 4 weeks using χ 2 analysis. Results: Symptoms decreased throughout the study using both child-reported ( F (9, 374) = 22.03, P < .001) and parent-reported scores ( F (9, 370) = 28.06, P < .001). Twenty-four (44.4%) children met the study definition for PPCS using the child-reported PCSI, while 20 (37.7%) children had PPCS using parent reports. The intervention did not significantly affect symptom resolution or PPCS rates. Conclusion: There is no benefit to prescribing 3D-MOT training for acute rehabilitation in pediatric patients with concussion and clinicians should instead focus on more effective programs.